Empowering Junior High School Students through Eco-Enzyme Production Training from Fruit Peel Waste: A Community Engagement Program at SMPIT Al-Qudwah, Tugumulyo District: Penelitian - Solina Balqis; Elva Febriyanti; Nurkayah; Muhammad Arif Fadillah; Lia Aseptin Murdini; Aldi Fahlefi; Hosiaroba; Viar Refri Zadin (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Organic waste management, particularly fruit peel waste, remains a challenge in school environments. Eco-enzyme production offers a simple and environmentally friendly solution that also supports environmental education. This community service program aimed to improve students’ knowledge and skills in managing fruit peel waste through eco-enzyme production training at SMPIT Al-Qudwah. The program was implemented using a hands-on training approach, including material delivery, direct practice, and evaluation using a pretest–posttest design involving 15 students. The results showed a clear increase in posttest scores compared to pretest scores, indicating improved understanding of organic waste management and eco-enzyme production. The training effectively enhanced students’ environmental awareness and practical skills, demonstrating the potential of experiential learning as a replicable model for school-based environmental education